2009
DOI: 10.1007/s10165-009-0198-5
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of neuropsychiatric systemic lupus erythematosus and potential biomarkers

Abstract: Systemic lupus erythematosus is a chronic, multisystemic, autoimmune disease that may involve the central, peripheral, and autonomic nervous systems and can present with a wide variety of neurological and psychiatric manifestations. In this article, we review the recent literature pertaining to the pathogenesis of neuropsychiatric systemic lupus erythematosus (NPSLE). We searched the PUBMED database with no chronological constraints using the following terms: "neuropsychiatric systemic lupus erythematosus" cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 96 publications
(115 reference statements)
0
31
0
4
Order By: Relevance
“…Anti-Rib-P antibodies were thought to be one of the biomarkers for NPSLE [12][13][14][15][16][17][18]. Anti-Rib-P antibodies and their associations with neuropsychiatric manifestations were also reported by Hassan et al [15] among Pakistani SLE patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Anti-Rib-P antibodies were thought to be one of the biomarkers for NPSLE [12][13][14][15][16][17][18]. Anti-Rib-P antibodies and their associations with neuropsychiatric manifestations were also reported by Hassan et al [15] among Pakistani SLE patients.…”
Section: Discussionmentioning
confidence: 89%
“…The same can be said about anti-neuronal nuclear antibodies (ANNA). How et al [17][18][19][20] had reported that ANNA antibodies were strongly associated with NP manifestations in SLE. In our study, the incidence of true anti-neuronal antibodies after absorption of ANNA showed no statistically significant difference the incidence of Rib-P antibodies between NPSLE and SLE patients without neuropsychiatric involvement.…”
Section: Discussionmentioning
confidence: 97%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Autoantibodies and immune-mediated vasculopathy was suggested in the pathogenesis of parkinsonism in NPSLE. 20 Kunas et al 4 found antibodies to dopaminergic cells in serum from the NPSLE patients manifested with parkinsonism. They concluded that antidopamine antibodies could be specific to NPSLE patients with parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, autoantibodies against the nerve cell body, axon, endothelial cells and histone, for example, are frequently recognized in NPSLE patients (11,12). One of the pathogenic mechanisms is thought to be that these antibodies induce apoptosis and alter expression level of adhesion molecules of endothelial cells in the blood-brainbarrier, allowing the passage of toxic components and antineuronal antibodies into the central nervous system (12).…”
Section: Discussionmentioning
confidence: 99%